2022
DOI: 10.3389/fnut.2021.783688
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Nutrition Interventions Improved Growth Performance and Intestinal Health via the Gut Microbiota in Piglets

Abstract: Intestinal infections in piglets are the main causes of morbidity before and after weaning. Studies have not explored approaches for combining pre-weaning and post-weaning nutritional strategies to sustain optimal gut health. The current study thus sought to explore the effects of early-life nutrition interventions through administration of synthetic milk on growth performance and gut health in piglets from 3 to 30 days of age. Twelve sows were randomly allocated to control group (CON) and early-life nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Subsequently, the paraffin blocks were sectioned at 5 μm thick sections using a semi-automatic microtome (LONGSHOU, China). Next, they were stained with hematoxylin and eosin according to methods of Luo et al (2021) , and observed under optical microscope and calculated histologic colitis score according to a pathology score system. Methods of pathology score system are described briefly below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the paraffin blocks were sectioned at 5 μm thick sections using a semi-automatic microtome (LONGSHOU, China). Next, they were stained with hematoxylin and eosin according to methods of Luo et al (2021) , and observed under optical microscope and calculated histologic colitis score according to a pathology score system. Methods of pathology score system are described briefly below.…”
Section: Methodsmentioning
confidence: 99%
“…The V3-V4 regions of bacterial 16S rRNA gene were amplified with the following primer set: 338F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′). The reaction system, determination of amplified fragments and purification were performed according to methods of Luo et al (2021) . The raw microbial sequence data were analyzed and processed by the Majorbio Bio-Pharm Technology Co. Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was used to collect serum and stools. Blood samples and stools were treated according to the method of Luo et al ( 2021 ). The estrus rate from day 8 to day 14 was statistically examined using all experimental yaks.…”
Section: Methodsmentioning
confidence: 99%
“…Testicular tissue section prepared method followed by Luo et al (20). Testicular tissue was immersed and fixed with Carnoy's solution for 24 h. Testicular samples were then removed from formalin and embedded in paraffin.…”
Section: Testicular Tissue Sections Preparationmentioning
confidence: 99%